IDENTIFIKASI GEN TERMOASIDOFILIK ALKOHOL 1 DEHIDROGENASE PADA BACILLUS SP-PJV - MS, Yulia Atika; Artika, I Made; Nurhidayat, Novik (Research Center for Biology-Indonesian Institute of Sciences, 2015)
One of the constrains in the conversion process of biomass to bioethanol is the unoptimum technology for the conversion process.One of the causes is the difference between optimum temperature for enzymatic hydrolytic saccharification and for fermentation.Enzymatic hydrolysis requires high temperature and acidic pH, while fermentation operates at mild condition.Hence, thermophilic fermentative microbes are needed so that simultaneous saccharification and fermentation processes can be carried out.Alcoholdehydrogenase(ADH), an enzyme functions in the final step of fermentation, catalyzes reduction of acetaldehydeto ethanol so that it being one of indicator fermentative microbial.Protium javanicum, a typical fruit from Lombok grow at high temperature and has sour taste so that it predicted has a thermo acidophilic ADH.This study was aimed toidentify gene encoding ADHin Protiumjavanicum(Pjv) microbial isolates.ADH gene identification was carried out by DNA amplification using spesific adh primers inqPCR machine. Results showed that all isolates tested had adh gene and that of Bacillus sp-Pjv was the most efficiently amplified. Results of fermentationtest also showed that the Bacillus sp-Pjv isolate was a better ethanol-producer than the others.